Edukasi Kesehatan dalam Upaya Pencegahan Penyakit Skabies di Pondok Pasantren Madrasah Tsanawiyah Harsallakum Kota Bengkulu - Inayah Hayati; Eka Nurdianty Anwar; Muhammad Yandi Syukri (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
Health Education in Efforts to Prevent Scabies at Islamic Boarding School of Harsallakum Madrasah Tsanawiyah Bengkulu Scabies is a skin disease caused by the Sarcoptes scabiei parasite that invades the skin of humans or animals. The high prevalence of scabies is generally found in environments with high population density and high interpersonal contacts such as prisons, Islamic boarding schools, and orphanages. There has been no research on the prevalence of scabies in the Harsallakum Islamic Boarding School, Bengkulu city. However, based on information from the school, there were several students who have been infected by skin disease with clinical symptoms of scabies. This community service program was aimed to provide education to students about preventing scabies infection. The service activities included delivering material about scabies, distributing leaflets, post-test and pre-test. This activity was attended by 65 participants. Evaluation included pre-test and post-test about the education carried out. The instrument to measure the level of students' understanding was the form of a questionnaire. The average value of the pre-test was 55.18 while the average value of the post-test was 80.26. It was concluded that this educational activity could increase the knowledge of the students of the Harsallakum Islamic Boarding School in Bengkulu about scabies disease. To optimize the prevention of scabies transmission, it is recommended to increase health education activities by involving health workers.